2014
DOI: 10.3103/s0095452714030050
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration ability of diploid and autotetraploid plants of Cichorium intybus L.

Abstract: 37 Polyploidy has played a significant role in the evolutionary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…With these advantages, mass phenotyping and characterizing of new plants are now a possible task. Our study is in agreement with that of the induced polyploid plants of Cichorium intybus ( Ravandi, Rezanejad & Dehghan, 2014 ) and Dendrobium officinale ( Pham et al, 2019 ). The explants of induced polyploid of D. officinal produced a higher protocorm induction rate but required a longer time for protocorm initiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With these advantages, mass phenotyping and characterizing of new plants are now a possible task. Our study is in agreement with that of the induced polyploid plants of Cichorium intybus ( Ravandi, Rezanejad & Dehghan, 2014 ) and Dendrobium officinale ( Pham et al, 2019 ). The explants of induced polyploid of D. officinal produced a higher protocorm induction rate but required a longer time for protocorm initiation.…”
Section: Discussionsupporting
confidence: 92%
“…The explants of induced polyploid of D. officinal produced a higher protocorm induction rate but required a longer time for protocorm initiation. According to Ravandi, Rezanejad & Dehghan, (2014) , the ability to regenerate shoots from callus or organogenesis in induced polyploid explants was significantly reduced. Tsukaya (2008) reported that Arabidopsis thaliana with more than eight sets of homologous chromosomes will display high ploidy syndrome, exhibiting contrasting effects by producing bigger cell in volume but smaller leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, enhanced synthesis of phytochemical compounds through artificial chromosome doubling has been intensively investigated. Autotetraploid plants of Cichorium intybus accumulated higher contents of phenolic compounds than control plants [57]. In colchicine-induced polyploid Artemisia annua, tetraploid plants have increased artemisinin contents compared with that of diploid plants [58].…”
Section: Discussionmentioning
confidence: 94%
“…To name only a few, Ginger tuber can be processed into soy sauce to be accessary food, and chrysanthemum is popular table vegetable in China. In addition, many herbs of Compositae becomes healthy drink tea or herbal cuisine such as Cichorium intybus L., Artemisia annua L., Chamomilla recutita L. and that polyploidy in all the three health medical herbs were reported concerning morphological, physiological, cytological and phytochemical studies [129][130][131][132][133]. For instance, level of the total phenolic and chlorogenic acid content in the leaves of tetraploid Cichorium intybus was reported significantly enhanced [129].…”
Section: Artificial Polyploidy Induction In Medicinal Herbs Of Compos...mentioning
confidence: 99%